2008
DOI: 10.1007/s00221-008-1364-2
|View full text |Cite
|
Sign up to set email alerts
|

Manual asymmetries in grasp pre-shaping and transport–grasp coordination

Abstract: Few studies have directly compared the visuo-motor transformation of grasp pre-shaping or transport-grasp coordination of reach-to-grasp movements between the two hands. Our objective was to determine if there are manual asymmetries in right-handed adults as a foundation to investigate hemispheric specialization in individuals post-stroke. Twelve non-disabled right-handed adults performed rapid reach-to-grasp movements to cylinders of three sizes as vision of the arm and hand was partially occluded. We reasone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 53 publications
4
39
0
Order By: Relevance
“…The unidimensional interpretation of our results is supported by contemporary systems and dynamic action theoretical models of motor control, which suggest that UE movement is organized through a series of highly interconnected neural networks 50 and tailored to the performance of tasks with specific behavioral goals. 2,15 Trombly and Wu 3 and Wu et al 4 showed that movement patterns displayed during performance of nonfunctional motor tasks were distinctly different from patterns displayed during goal-oriented motor performance.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The unidimensional interpretation of our results is supported by contemporary systems and dynamic action theoretical models of motor control, which suggest that UE movement is organized through a series of highly interconnected neural networks 50 and tailored to the performance of tasks with specific behavioral goals. 2,15 Trombly and Wu 3 and Wu et al 4 showed that movement patterns displayed during performance of nonfunctional motor tasks were distinctly different from patterns displayed during goal-oriented motor performance.…”
Section: Discussionsupporting
confidence: 70%
“…For example, the strong 2-factor CFA interfactor correlation may suggest the integration of the visuomotor neural pathways underlying reach and grasp 2,15,50,52,54,61 ; the item difficulty hierarchy may suggest a progression of task difficulty, proceeding from more simple (single joint) to more complex (multiple joint), and further may be related to the information processing requirements of the task (ie, amount of precision, number of performance steps, and biomechanical load). 2,6,7,23,56-58 …”
Section: Discussionmentioning
confidence: 99%
“…These differences between left-and right-handed reach-to-grasp actions are conspicuously absent in many previous grasping studies. Kinematic asymmetries favoring the dominant hand in reach-topoint actions are well documented (Boulinguez et al 2001a;Carson et al 1990Carson et al , 1993Elliott and Chua 1996;Elliott et al 1993;Fisk and Goodale 1985;Elliott 1986, 1989;Velay et al 2001), whereas multiple studies have demonstrated that manual asymmetries in the reach-to-grasp movement are subtle, if not altogether absent (Begliomini et al 2008;Flindall 2012;Flindall et al 2014;Grosskopf and Kuhtz-Buschbeck 2006;Tretriluxana et al 2008). The kinematic asymmetry recently identified during grasp-to-eat movements was interpreted as a right-hand/left-hemisphere advantage for eating, because participants produced smaller MGAs to eat while using their right hand only (Flindall and Gonzalez 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing right-and left-hand kinematics for grasping movements have shown few, if any, asymmetries between the hands (e.g., Grosskopf and Kuhtz-Buschbeck 2006;Tretriluxana et al 2008). These studies used placement tasks in which participants were asked to pick up a solid geometric shape and place it in a nearby location, an action which, one might argue, has little ecological relevance.…”
mentioning
confidence: 99%
“…This finding strongly suggests that hand preference for grasping did not influence participants’ space use with respect to the LF quadrant. Finally, investigations of kinematics of left- and right-handed reach-to-grasp movements have revealed, at most, minimal differences between hands (6063) suggestive that the preference to use the right hand (particularly in right space) is not driven by a kinematic advantage.…”
Section: Discussionmentioning
confidence: 99%